The correlation between serum uric acid and diabetic kidney disease in type 1 diabetes patients in Anhui, China - Jun Jiang; Xiaowan Zhou; Lei Lan; Wei Ren (BMC Nephrology, 2023)
Abstract Background/Aim To assess the correlation between serum uric acid (UA) level and diabetic kidney disease (DKD) in Type 1 diabetes (T1DM) patients in Anhui, China. Methods A total of 231 patients diagnosed with T1DM in our hospital were enrolled between January 2014 and December 2016. Urinary albumin-creatinine ratio (ACR) in patients with hyperuricemia was compared with those without hyperuricemia. The relationship between serum UA level and urinary ACR was examined by Spearman's correlational analysis and multiple stepwise regression analysis. The binary logistic multivariate regression analysis was performed to analyze the correlated factors for type 1 DKD. Results The average serum UA levels were 257.7 [215.0, 338.0]μmol/L. The median levels of urinary ACR were significantly higher in patients with hyperuricemia than those without hyperuricemia. In multiple stepwise regression analysis, Serum UA levels were positively correlated with the urinary ACR. The logistic multivariate regression analysis showed that hyperuricemia (OR: 5.24, 95% CI: 1.40—19.65, P = 0.014) had an independent positive correlation with DKD in T1DM patients, and the odds of Serum UA to DKD were both elevated as the serum UA levels rose no matter whether adjustment for traditional confounders. The area under the receiver operating characteristic curve was 0.62 (95% CI: 0.55–0.70) in assessing the discrimination of the serum UA level for DKD in T1DM patients. Conclusions In Chinese patients with T1DM, the serum UA level is positively correlated with urinary ACR and DKD. The correlation between Serum UA and DKD gradually increases with serum UA levels. Serum UA level is not a good predictor for DKD in T1DM patients. Serum UA may directly contribute to initiating DKD, while it has little direct but an indirect effect on an already established DKD in T1DM patients.